Multienvironmental Evaluation of Dry Pea and Lentil Cultivars in Montana using the AMMI Model. Issue 2 (1st March 2016) - Ito, Dai; Afshar, Reza Keshavarz; Chen, Chengci; Miller, Perry; Kephart, Ken; McVay, Kent; Lamb, Peggy; Miller, John; Bohannon, Brooke; Knox, Martha
Abstract : Rapid development of the Montana pulse crop industry has created a strong demand for breeding efforts and cultivar recommendations. We evaluated adaptation and yield stability of diversely sourced dry pea ( Pisum sativum L.) and lentil ( Lens culinaris Medik.) genotypes across Montana from 2009 to 2011. Mega‐environments in Montana and superior genotypes were identified using additive main effect and multiplicative interaction (AMMI) methodology. Grain yield of both crops varied among the locations and across years. A large portion of the total variation (genotype [G] and environment [E] plus their interaction G × E) was explained by E (93% for dry pea and 89% for lentil), while G only explained 0.7% and 3.6% of the total variation for dry pea and lentil, respectively. Dry pea cultivars Delta, Majoret, and Cruiser were found to be suitable, with general adaptation to Montana. Three mega‐environments were identified for pea including: (i) Richland (northeastern Montana); (ii) Bozeman, Conrad, and Corvallis (southwestern and western Montana); and (iii) Havre, Moccasin, and Huntley (northern, central, and southern Montana). Among lentil cultivars, CDC Richlea was judged as the most promising cultivar as a result of general adaptation. Lentil cultivars Essex and LC01602300R showed higher yield potential than CDC Richlea but more specific adaptation. Four mega‐environments were also distinguished for lentil including (i) Creston and Conrad (northwestern Montana), (ii) Havre and Richland (northern and northeastern Montana), (iii) Moccasin (central Montana), and (iv) Huntley (southern Montana).